Design of Dual-band low profile rectangular microstrip patch antenna using FR4 substrate material for wireless applications. (2021) - Sandhiyadevi, P.; Baranidharan, V.; Mohanapriya, G.K.; Roshini Roy, J.; Nandhini, M.
Abstract: In recent days, wireless technology getting more advanced to fulfil the user requirement. Based on this the design for achieving the requirement is still under researching to overcome the drawbacks in existing design. Many number of antenna design with lightweight, cost effective are proposed with various frequency ranges but still has some backlogs. In this paper, the new improved rectangular microstrip patch antenna design for wireless communication like WiMAX, WLAN etc. was proposed along with its improved design parameters like impedance matching, gain, voltage standing wave ratio, return loss. Then radiation pattern also simulated for both E-plane and H-plane by using the HFSS software. This proposed design utilizes the bandwidth effectively within the desired frequency range of (3.3–5.2) GHz to obtain the high efficiency.